2019
DOI: 10.3390/app9040673
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Dichroic-Prism-Based Multi-Perspective Digital Image Correlation System

Abstract: A robust three-perspective digital image correlation (DIC) system based on a cross dichroic prism and single three charge-coupled device (3CCD) color cameras is proposed in this study. Images from three different perspectives are captured by a 3CCD camera using the cross dichroic prism and two planar mirrors. These images are then separated by different CCD channels to perform correlation calculation with an existing multi-camera DIC algorithm. The proposed system is considerably more compact than the conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The issue of calibrating several independent benches using valuable CAD information is discussed in [11]. Conversely, when non-planar tests are to be instrumented at small scales or in conditions of difficult access, stereo can be used with a single camera by adapting the mounting with, for example, prisms and mirrors [12]. Another variant of DIC, which is still in its infancy, relies on X-ray based digital volume imaging.…”
Section: Advances In Dicmentioning
confidence: 99%
“…The issue of calibrating several independent benches using valuable CAD information is discussed in [11]. Conversely, when non-planar tests are to be instrumented at small scales or in conditions of difficult access, stereo can be used with a single camera by adapting the mounting with, for example, prisms and mirrors [12]. Another variant of DIC, which is still in its infancy, relies on X-ray based digital volume imaging.…”
Section: Advances In Dicmentioning
confidence: 99%
“…Contemporary numerical models require precise measurements of experimental curves and strength parameters. DIC measurement is currently the most important and constantly developed non-contact strain measurement method [18][19][20][21]. Its most significant 3D version has been extended to numerous research fields, including standard materials such as metals, plastics or thermoplastics [22], advanced polymeric composites [23], and biological materials such as tissues [24] or carotid arteries [25].…”
Section: Introductionmentioning
confidence: 99%
“…Logarithmic strains are more relevant in the case of high stra occurring in the necking area of the ductile metal alloy specimen than in the case of en neering strains [5,6]. DIC measurement is currently the most important noncontact strain measurem method and is constantly being further developed [7][8][9][10]. The most significant 3D vers is applied to research of standard metals, plastics, thermoplastics [11], advanced p meric composites [12], biological materials such as tissues [13] and carotid arteries [14 balloons [15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous examples of studies in which material strength investigations and mi fractography research were combined to extend the investigations can be found in contemporary literature [16][17][18][19][20], some of which deal with investigations at different t perature levels. DIC measurement is currently the most important noncontact strain measurement method and is constantly being further developed [7][8][9][10]. The most significant 3D version is applied to research of standard metals, plastics, thermoplastics [11], advanced polymeric composites [12], biological materials such as tissues [13] and carotid arteries [14] or balloons [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation